Can CEO dismissals be proactive? - Ertugrul, Mine; Krishnan, Karthik (Journal of Corporate Finance, 2011)
We find significant variation in the prior stock returns of firms that dismiss their CEOs between 1996 and 2008. 49% of firms that dismiss their CEOs do so in the absence of negative industry-adjusted stock returns prior to dismissal (37% dismiss in the absence of negative raw returns). We find evidence for two reasons why boards may dismiss CEOs early, i.e., in the absence of significant poor prior stock performance. First, we find that early dismissals are more likely to be associated with corporate scandals, suggesting that CEOs that are found to engage in unethical or illegal activities are dismissed although their actions may not have a significant adverse impact on firm value. Second, we find support for the argument that early dismissals are proactive actions by boards to dismiss low ability CEOs. We find that firms with more equity-based compensation for directors and higher independent director ownership are more likely to dismiss their CEOs early. Boards with strong incentives are more likely to be proactive and act on their private information about the CEO than boards with poor incentives. Early dismissal firms experience a short-lived decline in operating performance around the date of CEO dismissal, and their operating performance recovers immediately after the CEO is replaced. On the other hand, the operating performance of late dismissal firms declines significantly prior to dismissal and improves substantially after dismissal. We also find that CEOs that are dismissed early are not more likely to find new CEO positions than CEOs that are dismissed late, supporting the idea that early dismissal CEOs may not have different ability than late dismissal CEOs.